An enrollment and financial projection for Sta. Cruz Institute, Ilocos Sur for SY 1985 to 1988 - Taguiling, Mary Rose C. (Animo Repository, 1985)
This study aims to undertake an enrollment and financial projection for Sta. Cruz Institute, Sta. Cruz, Ilocos Sur for the school years 1985-1986, 1986-1987 and 1987-1988.The study used the historical-descriptive method of research. Analysis and projections of the enrollment were made using the average growth rate for the incoming first year students and the average retention rate for the higher year levels. For the financial analysis, the common size percentages, trend ratios and cost per student were employed. With respect to financial projection, the school fees for SY 1984-85 served as the basis for projected school fees for the next three years. Likewise, the cost per student/expense item in 1984-85 was the basis in projecting the cost of expenditures for the next three years. From the findings of the study, the following conclusions were derived: 1. The enrollment of SCI over the past five years fluctuated. However, the projected enrollment for the next three years was towards a gradual increase in enrollment. 2. SCI had been spending more than its financial resources which was mainly derived from tuition and other school fees. 3. Financial projections revealed that the school would continue to suffer losses inspite of the 20 percent increase in school fees and the minimal increase in enrollment.